2008
DOI: 10.1007/s00167-008-0525-y
|View full text |Cite
|
Sign up to set email alerts
|

Knee arthrodesis with an intramedullary nail: a retrospective study

Abstract: A group of 19 patients who underwent knee arthrodesis with use of an intramedullary nail between 1996 and 2005, was studied. In the majority of patients knee arthrodesis was performed as a salvage procedure for the limb following an infected total knee arthroplasty. The outcome of the procedure was evaluated with radiographs, the SF-36 score and the Oxford 12-item knee score. The functional result of a successful arthrodesis was found to be comparable with that of a revised hinged total knee arthroplasty. Knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Of these options, IM nails are reported to provide greater stability, avoid pin-tract infection, and allow faster weight-bearing, and several authors have reported good results with internal fixation arthrodesis with IM nailing. 3 , 4 , 7 8 9 10 11 , 18 , 20 However, fusion with an external fixator is a reasonable option when dictated by patient circumstances, such as a poor soft-tissue envelope or anatomy. 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these options, IM nails are reported to provide greater stability, avoid pin-tract infection, and allow faster weight-bearing, and several authors have reported good results with internal fixation arthrodesis with IM nailing. 3 , 4 , 7 8 9 10 11 , 18 , 20 However, fusion with an external fixator is a reasonable option when dictated by patient circumstances, such as a poor soft-tissue envelope or anatomy. 4 …”
Section: Discussionmentioning
confidence: 99%
“… 1 , 7 , 8 , 10 11 12 13 14 15 16 17 The reported limb-length discrepancy after arthrodesis ranged from 2.76 to 5.5 cm. 1 , 7 , 8 , 10 , 12 , 15 16 17 18 …”
mentioning
confidence: 99%
“…IMN is a popular method of arthrodesis and can be performed as a single [62-67] or two-stage revision procedure following debridement, cement spacer insertion and a period of intravenous antibiotics [68, 69] with or without the addition of bone grafts [70]. …”
Section: Methodsmentioning
confidence: 99%
“…The authors reported 83.3% fusion rates following this strategy [68]. Various implants have been used as an IMN device including the long arthrodesis IMN [62, 63], customized modular IMNs [64, 65], modular cemented IMNs [66], the Huckstep nail [69], [70], the curved Kuntscher nail [67] and the Wichita fusion nail [71]. Different designs have also been used for EF.…”
Section: Methodsmentioning
confidence: 99%
“…These implants have given fusion in 90–100% of cases regardless of the initial diagnosis or experience of the user (Domingo et al 2004, McQueen et al 2006, De et al 2008). However, many clinicians have been reluctant to use this technique due to the perceived difficulty in or impossibility of removing these nails without disrupting the fusion, to allow the management of associated complications such as infection.…”
mentioning
confidence: 99%